Knowledge, attitude, and practice of dental implants among dental postgraduates and practitioners in Davangere City, Karnataka: A cross-sectional study - Disha Nagpal; Shobha Prakash; Dheeraj D Kalra; Gagandeep Singh (Wolters Kluwer Medknow Publications, 2018)
Background: Implant therapy has become an important part of treatment to restore function and esthetics in partially/completely edentulous patients. Inspite of the progress made in implant dentistry since its inception, there have been some loopholes in scientific based knowledge and established clinical experience amongst dental professionals and postgraduates.So,an analysis was performed of the real picture. Objectives: A study was conducted to assess and compare the knowledge, attitude and practice of dental implants among dental postgraduate students and dental practitioners (General and institutional)in Davangere City, Karnataka and to identify the variations in their knowledge, attitude and practice with respect to dentist's factors (years of experience, implant training and their specialization). Materials and Methods: A cross sectional questionnaire based survey was conducted using census approach with informed consent. A pretested, self administered questionnaire containing demographic details and knowledge ,attitude and practice based questions was distributed and collected back from the respondents. Responses were coded before and decoded after the analysis. Statistical analysis was performed using SPSS SoftwareV17.0. Results: The results were determined after the statistically analyzed and concluded that the knowledge was widespread among postgraduates and dental practitioners and variations existed amongst the subjects with respect to age, gender, years of experience, practice type, implant training and their specialization. It was also found that the attitude and practice towards implants and their evidence based knowledge about the same was variable.